Time after Time: Narratives of the Longue Durée in the Anthropocene - Stephen W. Sawyer (Transatlantica)
This article suggests that new potential areas of collaboration between historians and literary scholars have emerged around a nascent but galloping interest in two fields of scholarship, the Anthropocene and the longue durée. Building on the tradition of the Annales school, and in particular the contributions of Fernand Braudel, this article argues that while there is a growing consensus about the necessity of trans-national and trans-temporal history, the critical implications of this enterprise for thinking historical and literary narrative have remained highly unsatisfying. Any return to the longue durée necessitates a deep reconsideration of the social scientific foundations of the longue durée in its previous manifestations, especially its conception of the nature-culture relationship, and an acknowledgement of the limitations of these earlier formulations for thinking about longer time scales and beyond national boundaries today. Following recent work in anthropology that has attempted to break down the nature-culture barrier, this article suggests that the Anthropocene has generated a new arrangement of temporal scales and therefore a poignant rearticulation of the long and short durée as well as the agency that drives action within these two realms.